A patient with lower gastrointestinal bleeding: common history, very uncommon cause, minimally invasive treatment - Lock, Guntram; Daniels, Thies; Kock, Lars (Zeitschrift für Gastroenterologie, 2018)
An 81-year-old patient with significant cardiac comorbidities, a history of sigmoid resection 6 years ago, and iliac bypass surgery 19 years ago presented with mild hematochezia for the previous 3 days. While hemodynamically stable at first, he developed massive bleeding during preparation for colonoscopy and underwent a short course of cardiopulmonary resuscitation. Colonoscopy revealed no active bleeding but a protuberance of the colonic wall and a coagulation clot. In ultrasonography immediately after endoscopy, a large aneurysm was diagnosed and diagnosis of an iliaco-colonic fistula was assumed. CT scan demonstrated a large pseudoaneurysm of the distal anastomosis after iliaco-iliac bypass. With endovascular treatment, the original lumen of the iliac artery could be recanalized, and 2 covered stents were placed to cover both anastomosis of the prosthetic bypass leading to a complete shutdown of bypass perfusion. A double-barreled transversostoma was established to minimize contamination of the aneurysmal sac. Seven months after these procedures, the patient is well and free of infection.Though aorto- or iliaco-colonic fistula after aortic or iliac surgery are very rare, endoscopists should be aware of their possibility. A high index of clinical suspicion in patients with prior abdominal vascular bypass surgery should prompt rapid imaging studies, possibly before endoscopy. In critically ill patients, endovascular treatment may be a suitable alternative and result in a favorable outcome.
Keywords: lower gastrointestinal bleeding; aortoenteric fistula; iliaco-colonic fistula; aneurysm